Основные фонды и производственные мощности в горной промышленности - Иванов Н. И. Николай Иванович; Ефремов А. В. Алексей Владимирович; Долгий В. И. Владимир Иванович; Бреславцев А. В. (Москва, Недра, 1984)
Авт. указаны на обороте тит. л.